2019
DOI: 10.7717/peerj.7058
|View full text |Cite
|
Sign up to set email alerts
|

Expression of osteopontin, matrix metalloproteinase-2 and -9 proteins in vascular instability in brain arteriovenous malformation

Abstract: Background Matrix metalloproteinase (MMP)-2 and -9 are Osteopontin (OPN) dependent molecules implicated in the destabilization of blood vessels. OPN and MMPs have been studied in brain arteriovenous malformation (BAVM) patients’ tissues and blood samples before intervention. In this study, we compared the serum level of these markers before and after treatment, as well as assessed their protein expressions in BAVM tissues to evaluate their roles in this disease. Methodology Serum samples from six BAVM patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The MMP‐9 levels rose further higher 24 h after embolization and surgery resection and then decreased to pretreatment levels during the follow‐up period. A study by Anbarasen et al (2019) showed elevated serum levels of MMP‐9 and MMP‐2 in bAVM patients before and after treatment, but the study was limited due to the lack of an appropriate follow‐up period. Taken as a whole, these results confirm that MMP‐9 could be used as a potential marker for inflammation.…”
Section: Downstream Inflammatory Mediators Involved In Bavm and Ichmentioning
confidence: 99%
“…The MMP‐9 levels rose further higher 24 h after embolization and surgery resection and then decreased to pretreatment levels during the follow‐up period. A study by Anbarasen et al (2019) showed elevated serum levels of MMP‐9 and MMP‐2 in bAVM patients before and after treatment, but the study was limited due to the lack of an appropriate follow‐up period. Taken as a whole, these results confirm that MMP‐9 could be used as a potential marker for inflammation.…”
Section: Downstream Inflammatory Mediators Involved In Bavm and Ichmentioning
confidence: 99%